Successful professional reviews for civil engineers - Waterhouse, Patrick; Steels, H. Macdonald (ICE Publishing, 2015)
'Successful Professional Reviews for Civil Engineers' provides a comprehensive guide to the constituent parts of the ICE Professional Review process, ideal for those engineers nearing the completion of their initial professional development.